2011
DOI: 10.1029/2010jd015233
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of positive and negative compact intracloud discharges

Abstract: [1] Prior studies have found that positive and negative compact intracloud discharges (+CIDs and −CIDs, according to the physics sign convection) occur at distinctly different altitudes, which correspond to different regions in a thunderstorm. On the basis of a large number of CIDs of both polarities recorded by our VLF/LF lightning location network, characteristic differences between +CIDs and −CIDs are discussed in this study. The results reveal that −CID is a more special type of discharge. Compared with +C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 20 publications
10
62
0
2
Order By: Relevance
“…Zhu et al () reported that 10 −NBEs and 67 +NBEs occurred during a 3‐hr observation period, and they found that the derived peak currents of some −NBEs are larger than those of the positive ones. Wu et al () also found that a considerably higher percentage of −NBEs (negative CIDs) than positive ones have large peak values of the normalized electric field changes in the VLF/LF band. The radiation field from a distant and vertical Hertzian dipole is proportional to the time deviation of the vertical current moment (e.g., Nickolaenko & Hayakawa, , p. 69).…”
Section: Discussionmentioning
confidence: 94%
“…Zhu et al () reported that 10 −NBEs and 67 +NBEs occurred during a 3‐hr observation period, and they found that the derived peak currents of some −NBEs are larger than those of the positive ones. Wu et al () also found that a considerably higher percentage of −NBEs (negative CIDs) than positive ones have large peak values of the normalized electric field changes in the VLF/LF band. The radiation field from a distant and vertical Hertzian dipole is proportional to the time deviation of the vertical current moment (e.g., Nickolaenko & Hayakawa, , p. 69).…”
Section: Discussionmentioning
confidence: 94%
“…Other authors (Rison et al, 1999;Wu et al, 2011) have shown that occasionally NBEs can initiate otherwise "ordinary" flashes. All of the cases in Fig.…”
Section: Comparison With Tipps Recorded By Autonomously Triggered Tatrmentioning
confidence: 99%
“…Another name employed for this unique stroke is "compact intracloud discharge", or CID (see, e.g., Nag et al, 2010). NBEs, and their accompanying VHF pulse, were originally reported in 1980 (Le Vine, 1980) and have been observed by many workers since (e.g., Hamlin et al, 2007;Holden et al, 1995;Jacobson, 2003a, b;Light, 2003, 2012;Jacobson and Heavner, 2005;Jacobson et al, 2007Jacobson et al, , 2011Massey and Holden, 1995;Massey et al, 1998;Nag andRakov, 2009, 2010a, b;Nag et al, 2010;Rison et al, 1999;Smith et al, 1999b;Thomas et al, 2001;Watson and Marshall, 2007;Wu et al, 2011Wu et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a ground-based study of NBEs (Nag et al, 2010) observed that out of a total of 157 events, 73 % were isolated. A more extensive survey of 11 876 NBEs in China (Wu et al, 2011) finds that neighbors are very improbable (<2 %) in the 10 ms preceding an NBE, but are sometimes seen (∼12 % for positive-polarity NBEs, ∼4 % for negative-polarity NBEs) in the ten millisec following the NBE. This matter has important implication: Without a prior leader process to ionize the air and prepare a conductive channel, how can a large-scale charge transfer (stroke) occur?…”
Section: Goals Of the Present Studymentioning
confidence: 99%